Advantage of Early Liver Transplantation whenever Hepatocellular Carcinoma Recurrence after Primary Liver Resection. (July 2018) - Chan, Kun-Ming; Cheng, Chih-Hsien; Wu, Tsung-Han; Lee, Chen-Fang; Wu, Ting-Jung; Chou, Hong-Shiue; Lee, Wei-Chen
Abstract : Background: Liver transplantation (LT) following primary liver resection (LR) for Hepatocellular carcinoma (HCC) patients, also termed as salvage LT, has been consider as a promising strategy for improving patient's outcome. The study aimed to identify predictors of such patients from the primary LR to LT for HCC, and to provide additional information for decision-making in therapeutic strategy for patient with HCC. Methods: This is a retrospectively review of patients who had been undergone LR for HCC followed by LT for liver cirrhosis with or without recurrent HCC between May 2005 and February 2017. The clinicopathological features of the patients regarding LR and LT were analyzed to determine prognostic factors of patients after LT. Results: A total of 59 patients were enrolled in this study. During the follow up, three cases (5%) encountered hospital morality, and 15 patients (26.8%) developed HCC recurrence after LT. The recurrence-free survival at 1-, 3-, and 5-year were 84.8%, 68.2%, and 68.2%, and disease specific overall survival rates were 95.7%, 74.4%, and 66.7% at 1-, 3-, 5-year after LT, respectively. Three independent prognostic factors including UCSF transplantation criteria (p = 0.018, hazard ratio (HR) = 12.70), tumor size > 5cm at LR (p = 0.012, HR = 7.90) and period between HCC recurrence following LR and LT > 1 year (p = 0.030, HR = 7.57) were identified for HCC recurrence after LT. Conclusions: Tumor features of HCC at both LR and LT would play potential roles affecting HCC recurrence after LT. Importantly, LT should be considered as soon as possible whenever recurrent HCC of LR meet transplantation criteria and indicate for LT.